Exploring collective spatial distribution in basketball - Esteves, Pedro (2015)
this study aimed to analyse players’ spatial distribution according to their performance outcomes in basketball. Three competitive games of U14 portuguese basketball teams were filmed and then analysed in order to select 10 sequences of play ending in successful offense or successful defence. Movement displacement trajectories of performers were digitized in order to access their real world coordinates using TACTO software. This procedure allowed computing the number of attackers, defenders and ratio attackers/defenders on each of seven court locations (A1, A2, A3, A4, A5, A6 and A7) throughout the sequence of play, on a moment-to-moment basis. We found that player’s spatial distribution proceeds in function of the relative position to the basket. Particularly, defensive numerical superiority in closer areas to the basket (A3) was related with higher offensive efficacy. These results suggest that interacting constraints, probably related with the proximity to the basket, inefficacy of defensive skills and superior attacker mobility might have shaped distinctive collective patterns of spatial distribution.